Problematika Orang Tua dalam Pendampingan Belajar Anak Difabel Selama Pandemi Covid-19 di SMALB ABC YKAB Pulisen Boyolali - Kholifatul Khasanah (Counselle| Journal of Islamic Guidance and Counseling, 2022)
Abstract is written concisely that includes This research is entitled "The Problems of Parents in Learning Assistance for Children with Disabilities During the Covid-19 Pandemic at SMALB ABC YKAB Pulisen Boyolali (Analysis of Islamic Family Guidance and Counseling)". This research is motivated by the circumstances of parents who are currently required to accompany their children's learning. Due to the COVID-19 pandemic, the government has decided to teach online. This study used qualitative research methods. Qualitative research is one of the research procedures that produces descriptive data in the form of spoken or written behavior of the people being observed. This study aims to understand social phenomena more objectively. Qualitative research is used to gain a deep understanding of the phenomenon so that a theory will be obtained. This research is descriptive, namely the data collected in the form of words. The results of this study indicate that various problems that emerged, after the researchers conducted research on the learning assistance of children with disabilities at SMALB ABC YKAB Pulisen Boyolali during the Covid-19 pandemic, including the busyness of parents, economic difficulties, low parental education, and boredom of children in study. The analysis of the problems of parental assistance in children's learning uses the theoretical basis of the Islamic family counseling function, namely the religious function. This is a very important initial foundation for children so that children have peace of mind, inner peace when facing various kinds of problems. When parents have a strong religious foundation, the problems that arise when mentoring children's learning during the Covid-19 period can be avoided.